Upaya Meningkatkan Kualitas Sumber Daya Manusia melalui Strategi Persaingan Usaha Ekonomi Kreatif Menuju New Normal (Studi Kasus Pegadaian Cabang Pelayanan Syariah (CPS) Bangkalan) - Ismawati Ismawati; Mochammad Isa Anshori (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The objectives of this study include knowing how to develop the quality of human resources, the extent to which the competitive strategy in improving the quality of services will be applied towards the new normal, how to improve the quality of human resources and performance competition strategies in the new normal era. The method used in this research is descriptive qualitative research method. The results showed that CPS Bangkalan Pegadaian to improve or develop the quality of human resources through increasing creative economic strategies by means of improving several products and CPS Bangkalan Pegadaian systems, including the Digital Sharia Pawnshop Application (PSD), Amanah Financing, Gold Savings and Arrum. The product and system of the CPS Bangkalan Pegadaian that is in great demand by customers is gold savings. This product is in great demand because it is easy to access, the process is fast, and there are fewer requirements to fulfill. The obstacles faced are the lack of socialization to customers, the many requirements.